Produção de bio-óleo a partir da pirólise de casca de coco em leito fixo - Agrizzi, Tiago (2018)
The exploitation of energy resources is fundamental for the economic development of the countries, as the diversified energy matrix guarantees internal supply and mitigates the dependence on energy imports. About 81% of the world's energy demand comes from fossil fuels, which will be a scarce source in the future, and its exploitation will lead to several environmental problems. In view of this, the exploitation of biomass as a renewable energy source is highlighted. In this context, pyrolysis presents like a technology with potential for the conversion of biomass into energy products. Thus, a study of the behavior of the yield of the products formed in the conventional pyrolysis of the green coconut shell in a fixed-bed reactor was carried out from a factorial design 32. In the first stage, the biomass was characterized by the lignocellulosic composition, of the immediate analysis, elemental analysis, X-ray fluorescence and infrared vibrational spectroscopy. In the second stage, the thermal degradation kinetics of the coconut shell were evaluated from the thermogravimetric analyzes, the kinetic models available in the literature and the conventional pyrolysis was performed in a fixed bed reactor. Finally, the identification of the compounds in the bio-oil from pyrolysis was done by gas chromatography coupled to mass spectrometry detector. The calorific value of coconut husk, of 18.01 MJ/kg, 17.3 MJ/kg and 17.93 MJ/kg, was similar using different methodologies. The coconut shell has exploration potential in the generation of thermal energy. The isoconversion kinetic models of Ozawa, Starink and K-A-S were representative for the process. The activation energy found for coconut shell through kinetic models was between 75.95 and 84.51 kJ/mol. The temperature and particle diameter influenced the yield of conventional pyrolysis products in a fixed bed reactor. The maximization of the yield of the bio-oil, 49.45%, was obtained in run 7 with a temperature of 773.15K and an equivalent particle diameter of 2.394 mm. The characterization of the organic fraction of the bio-oil presented the class of the phenols mainly, that can be explored in the chemical and pharmaceutical industry. Coconut shell pyrolysis is an alternative for the exploitation of this agricultural residue.